Tradisi Nyuguh Tamu: Menyambut Kelahiran Bayi di Kampung Baru Desa Cipayung Kecamatan Padarincang Kabupaten Serang Banten - Muhammad Rizki; Siti Fauziyah; Muhammad Nandang Sunandar (Lembaga penelitian dan pengabdian kepada Masyarakat, 2026)
This study is motivated by the limited academic discussion regarding the Nyuguh Tamu tradition as a childbirth welcoming ritual in Kampung Baru, Cipayung Village, Padarincang District, Serang Regency, Banten. The research employs a qualitative method with an ethnographic approach through observation, in-depth interviews, and documentation, analyzed using the Miles and Huberman interactive model. The findings reveal that the Nyuguh Tamu tradition contains integrated religious, social, and cultural dimensions. The tradition functions not only as an expression of gratitude for the birth of a baby, but also as a means of strengthening social solidarity, reinforcing kinship relations, and preserving local cultural values. Each stage of the ritual symbolizes hopes for safety, health, prosperity, and social acceptance of the newborn. Furthermore, community involvement in the implementation of the tradition reflects strong values of mutual cooperation, togetherness, and reciprocity that continue to survive amid modernization. Therefore, Nyuguh Tamu represents a form of local wisdom that remains relevant in maintaining the cultural identity of the community.